Removal of methylene blue from aqueous solution by coconut coir dust as a low-cost adsorbent - Abdullah Al Ashik; Md. Ataur Rahman; Debadas Halder; Md. Mufazzal Hossain (Applied Water Science, 2023)
Abstract Adsorption of methylene blue (MB) from its aqueous solution onto coconut coir dust was studied in batch method. Coconut coir dust was characterized before and after adsorption by FT-IR spectroscopy and scanning electron microscopy (SEM). Surface charge, pHzpc of the adsorbent was measured by the method suggested by Huang and Ostovic and was found to be 7.65 (± 0.05). Batch kinetic experiments were performed and effects of several operational parameters i.e., contact time, initial concentration, pH of the solution and temperature on adsorption process were investigated. The effect of pH on adsorption was examined using a MB solution of 31.98 mg L−1 at 30 °C on coconut coir dust varying the pH range from 3.02 to 11.04. At basic condition, the uptake increased significantly and reached the maximum at pH 9.0. The batch adsorption model, based on the assumptions of the Lagergren’s pseudo-first order and the Ho’s pseudo-second order model were applied to investigate the kinetics of this adsorption process. The results showed that the kinetic data fit very well to the pseudo-second order kinetic model. The adsorption isotherms were determined at four different particle sizes which ranges from < 106 to 300 μm. Among them < 106 μm particle size was chosen for whole process because of comparatively good adsorption capacity. The adsorption isotherms at different temperatures maintaining pH at 7.68 were studied and results show that the amount adsorbed increases with the increase in the temperature under all conditions. The linear correlation coefficients indicate that the Langmuir isotherm best fitted with the experimental data. Thermodynamic parameters such as Gibbs free energy change (ΔG), enthalpy change (ΔH) and entropy change (ΔS) were calculated. The values of ΔH and ΔS were found to be + 30.16 kJ mol−1 and + 0.128 kJ mol−1 K−1 , respectively. At pH 7.68, the present system was spontaneous and endothermic in nature. It was found that when the temperature was increased from 303 to 333 K, the ΔG value decreased.